2014
DOI: 10.1002/ejoc.201402068
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐ vs. Dinuclear Gold‐Catalyzed Intermolecular Hydroamidation

Abstract: Mono‐ and dinuclear gold catalysts were investigated in the intermolecular hydroamidation of olefins. Upon activation of [Ph3PAuCl] and [xantphos(AuCl)2] with various silver salts (AgOTf, Ag[BF4], and Ag[SbF6]), diverging reactivity of the resulting cationic gold complexes was observed. It was found that both the binding ability of the counterion and the solvent have a significant impact on the reactivity of the mono‐ and dinuclear complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…of AgSbF6, in N,N'-DMF at 60 °C for 5 h led to full conversion and high regioselectivity to B (95-100%), as determined by 1 H Having established that ligands L1 and L2 can facilitate pre-activation of C≡C bonds in a σ,π-fashion, we wondered about their activity in the heterocyclization (intramolecular hydroamination) of urea-functionalized alkyne A. Previously, Paradies and co-workers compared AuCl(Xantphos), Au 2 Cl 2 (Xantphos), and AuCl(PPh 3 ) for the intermolecular hydroamidation of cyclohexene (and analogs thereof) and toluene sulfonamide in the presence of stoichiometric amounts of silver salts as halide abstracting agents [17]. This study concluded that [Au 2 (Xantphos)] 2+ and the corresponding species [Au 2 (Xantphos) 2 ] 2+ , which forms from the former, were both catalytically inactive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of AgSbF6, in N,N'-DMF at 60 °C for 5 h led to full conversion and high regioselectivity to B (95-100%), as determined by 1 H Having established that ligands L1 and L2 can facilitate pre-activation of C≡C bonds in a σ,π-fashion, we wondered about their activity in the heterocyclization (intramolecular hydroamination) of urea-functionalized alkyne A. Previously, Paradies and co-workers compared AuCl(Xantphos), Au 2 Cl 2 (Xantphos), and AuCl(PPh 3 ) for the intermolecular hydroamidation of cyclohexene (and analogs thereof) and toluene sulfonamide in the presence of stoichiometric amounts of silver salts as halide abstracting agents [17]. This study concluded that [Au 2 (Xantphos)] 2+ and the corresponding species [Au 2 (Xantphos) 2 ] 2+ , which forms from the former, were both catalytically inactive.…”
Section: Resultsmentioning
confidence: 99%
“…Dual-gold catalysis, on the other hand, can lead to both σand π-activation (either of the same functional group within a substrate or of two separate functional groups) by two Au centers. The proximity of both Au-centers has occasionally been credited to enhance reactivity [15][16][17]. The prevailing strategy utilizes mononuclear Au(I) complexes to induce this mode of activation (Scheme 1) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the aromatic scaffold may serve as a reasonable N,N,N-donor for other low-valent transition metals or lanthanides. In the next step, an evaluation of catalytic activities will be explored, for example, in hydroarylation 97 or hydroamidation 98 reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, the hydroamidation of norbornene, an analogue to cyclohexene, with tosylamide gave 83% isolated yield in only 20 minutes reaction time (Scheme 32). 92…”
Section: Scheme 31 N-alkylation Using Hcl-activated Bentonite As Catamentioning
confidence: 99%